Peningkatan Aktifitas dan Hasil Belajar IPA Materi Struktur dan Fungsi Jaringan Tumbuhan Melalui Pembelajaran Kooperatif Tipe Time Token Siswa Kelas VIII.3 SMP Negeri 1 Kecamatan Harau Kabupaten Lima Puluh Kota - Netridaliyati Netridaliyati (Pendidikan Biologi FKIP UMMY, 2021)
The learning process that has been going on for science subjects is less varied, this results in learning outcomes that are not as expected. The purpose of this study was to improve the activities and learning outcomes of science class VII.3 semester 1 SMPN 1 Harau District through a time token type of cooperative learning model. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings on the material structure and function of plant tissue. This research was conducted from September to November 2017 semester 1 of the 2017/2018 academic year. The subjects of this research were all 32 students of class VIII.3 semester 1 of the 2017/2018 academic year. Data collection tools in this study were observation sheets and test questions. The activity of students learning science has increased significantly in all indicators from the first cycle to the second cycle as well as learning outcomes. The increased activity of students learning physics from the first cycle to the second cycle is the impact of the Time Token type of cooperative learning. The conclusions of this study are 1) Time Token Cooperative Learning can increase the learning activities of class VIII.3 students of SMPN 1 Harau District, Lima Puluh Kota Regency on the material of plant tissue structure and function; 2) Cooperative Learning of the Time Token type can improve the learning outcomes of class VIII.3 students of SMPN 1 Harau District, Lima Puluh Kota Regency on the material of plant tissue structure and function.